MEMBANGUN PARIWISATA BERKELANJUTAN: EKOWISATA DI DESA TISTA, TABANAN, BALI - Juniawan, I Made (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Sustainable tourism is widely recognized as a solution that benefits the environment, economy, and social and cultural aspects. Ecotourism stands out as a tangible demonstration of sustainable tourism practices. Therefore, the focus of this research is on the implementation of ecotourism in Tista Village, Tabanan Regency, Bali. The main objective is to explore the effectiveness of implementing eco-tourism in mitigating negative impacts in the field of tourism. Using a qualitative approach that is conducted in a naturalistic setting. Purposive sampling technique is utilized to select informants. Data was collected through observation, document analysis, and structured interviews. The data collected are processed using descriptive qualitative, with data reduction steps to summarize the main elements, data submissions, as well as conclusions. The research findings that the implementation of ecotourism in Tista Village succeeded in providing various positive impacts for the community and the village, encompassing aspects such as the economy, social and cultural development, and the environment. The principles of sustainable tourism are also in line with this. Eco-tourism has increased public awareness of the importance of conserving the local environment and culture. One of the primary findings is the significance of community empowerment in ecotourism management.